Pesticide residue accumulation in buffalo ovaries: a potential hazard to fertility - RATNAKARAN, U; GHUMAN, S P S; BEDI, J S; GILL, J P S (The Indian Journal of Animal Sciences, 2014)
The present study was conducted on 58 female buffaloes subjected to slaughtering at a local abattoir. The study investigated the presence of pesticide residues in their blood, ovarian tissue as well as follicular fluid samples. These samples were subjected to gas chromatography (GC) to detect the presence of residues of organochlorine pesticides, organophosphorous pesticides and synthetic pyrethroids, followed by their confirmation using gas chromatography mass spectrometry (GCMS). About 32.7% blood, 53.4% ovarian tissue and 21.4% follicular fluid samples were found positive for pesticide residue(s) and their respective alarming levels of pesticide residues were 47.7±113.7 ng/ml, 124.3±106.1 ng/g and 245.6±477.1 ng/ml. The most detected pesticide residues in the ovarian/ follicular fluid samples were DDT / endosulphan and their metabolites. In conclusion, a much higher load of pesticide residues in ovarian/follicular fluid of buffaloes as comapred to their blood suggested the potential hazard of these residues to fertility status of buffaloes.